2023
DOI: 10.1021/acs.jafc.3c04606
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry and Blackberry Anthocyanins Ameliorate Metabolic Syndrome by Modulating Gut Microbiota and Short-Chain Fatty Acids Metabolism in High-Fat Diet-Fed C57BL/6J Mice

Lanlan Du,
Han Lü,
Yan Chen
et al.

Abstract: In this study, blueberry (Vaccinium ssp.) anthocyanins (VA) and blackberry (Rubus L.) anthocyanins (RA) were used to investigate the effects on metabolic syndrome (MetS) and the potential mechanisms. Importantly, all of the data presented in this study were obtained from experiments conducted on mice. As a result, VA and RA reduced body weight gain and fat accumulation while improving liver damage, inflammation, glucose, and lipid metabolism induced by a high-fat diet. Moreover, VA and RA regulated the gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 85 publications
2
1
0
Order By: Relevance
“…For example, in our study, no impact on Bacteroidetes and Firmicutes from HFEB was observed. This is in line with observations from a study using freeze-dried strawberries but not with studies based on extracts from berries. , In addition to the possible discrepancy in dietary lipids, it is plausible that the inclusion of high amounts of nutrient-deprived fruit extracts is often not matched appropriately in protein and carbohydrate content, which can lead to spurious effects on Bacteroidetes and Firmicutes. On the other hand, we report an increased abundance of Actinobacteria and Verrumicrobia (and Tenericutes), phyla that have repeatedly (alone or in combination) been associated with anthocyanin-based dietary interventions. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, in our study, no impact on Bacteroidetes and Firmicutes from HFEB was observed. This is in line with observations from a study using freeze-dried strawberries but not with studies based on extracts from berries. , In addition to the possible discrepancy in dietary lipids, it is plausible that the inclusion of high amounts of nutrient-deprived fruit extracts is often not matched appropriately in protein and carbohydrate content, which can lead to spurious effects on Bacteroidetes and Firmicutes. On the other hand, we report an increased abundance of Actinobacteria and Verrumicrobia (and Tenericutes), phyla that have repeatedly (alone or in combination) been associated with anthocyanin-based dietary interventions. …”
Section: Discussionsupporting
confidence: 82%
“…Several other studies have also reported on the effect of dietary polyphenols on Akkermansia. A recent discussion on the prebiotic expansion of Akkermansia describes how polyphenols prohibit the growth of opportunistic and/or pathogenic bacteria while creating niches for health-promoting populations to thrive, thereby exerting both protective effects on the colonic environment as well as fueling phenolic metabolite production . A recent study claimed that dietary anthocyanins reduced the amount of Bifidobacterium in mice gut microbiota, but the surprising increase of Bifidobacterium by the HFD prevents comparison with the current findings. Indeed, Bifidobacterium species have long been known to be among the most active polyphenol metabolizers among the gut microbiota, and Bifidobacterium are reported to increase with dietary intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Du et al [19] demonstrated that FBT could enhance the abundance of Prevotella, the same as the present data. Du et al [53] proved that the increased abundance of Bifidobacterium in the mice fed by HFD, likely to be associated with polysaccharide and other complex carbohydrates consumption and indicating the gut microbiota imbalance or inflammatory response, was reduced by blueberry anthocyanins and blackberry anthocyanins administration, which is similar to this study. KEGG analysis of the detected gut microbiota revealed that carbohydrate, amino acid, and lipid metabolism were dominantly enriched metabolic pathways after different treatments.…”
Section: Flt and Fbt Exerted Anti-obesity Effects By Maintaining The ...supporting
confidence: 88%